PEMBUATAN SISTEM PENERANGAN SEL SURYA DI PEMANDIAN SUMBERWRINGIN - Denda Dewatama; Gillang Al Azhar; Imam Saukani; Subiyantoro Subiyantoro; Herwandi Herwandi; Bambang Priyadi (Jurnal Pengabdian kepada Masyarakat, 2023)
Sumberwringin bathhouse is located in Wringin Songo village and is a potential bathhouse to be developed by Wringin Songo village. Wringinsongo Village is located in Tumpang District and is one of the partner villages of Polinema. Wringinsongo Village. There is a lot of potential in Wriginsongo Village, namely the potential for agriculture, plantations, fisheries, livestock, and water resources. The local government of Malang Regency through Wringin Songo Village reads the situation as an opportunity to improve the welfare of its citizens. So that currently the spring functions as water tourism called Sumberwringin Baths which is managed by the village government as an attractive natural recreation facility. Sumberwringin baths have several shortcomings, namely still lacking in terms of lighting. The bath manager wants to install lighting around the bath by utilizing natural resources, namely sunlight. So solar cell lighting is needed in the area, namely in Sumberwingin baths by utilizing sunlight (PLTS) for lighting in the area.